A versatile method for cyclic polymers from conjugated and unconjugated vinyl monomers. Issue 17 (13th August 2019) - Liu, Xueping; Chen, Ji‐Qiang; Zhang, Minghui; Wu, Ying; Yang, Miao; Zhang, Ke
ABSTRACT: A versatile method was introduced to prepare cyclic polymers from both conjugated and unconjugated vinyl monomers. It was developed on the combination of the RAFT polymerization and the self‐accelerating double strain‐promoted azide‐alkyne click (DSPAAC) reaction. In this approach, a switchable chain transfer agent 1 was designed to have hydroxyl terminals and a functional pyridinyl group. The protonation and deprotonation of pyridinyl group endowed the chain transfer agent 1 with a switchable control capability to RAFT polymerization of both conjugated and unconjugated vinyl monomers. Based on this, RAFT polymerization and the following hydroxyl end group modification were used to prepare various azide‐terminated linear polymers including polystyrene, poly( N ‐vinylcarbazole), and polystyrene‐block‐poly(N‐vinylcarbazole). Using sym‐dibenzo‐1, 5‐cyclooctadiene‐3, 7‐diyne (DBA) as small linkers, the corresponding cyclic polymers were then prepared via the DSPAAC reaction between DBA and azide terminals of the linear precursors. Due to the self‐accelerating property of DSPAAC reaction, this bimolecular ring‐closing reaction could efficiently produce the pure cyclic polymers using excess molar amounts of DBA to linear polymer precursors. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2019, 57, 1811–1820 Abstract : A versatile method was introduced for the formation of cyclic polymers from both conjugated and unconjugated vinyl monomers. In this approach, well‐defined linear polymers were synthesized by RAFT polymerization with a switchable chain‐transfer agent, which was then ring‐closed by a self‐accelerating double strain‐promoted azide‐alkyne click reaction to form the corresponding cyclic polymers.